1999
DOI: 10.1177/112070009900900306
|View full text |Cite
|
Sign up to set email alerts
|

Cemented Hip Replacements in Patients Younger than 50 Years: 16–24 Year Results

Abstract: Although specialist centres have recorded a 75% survivorship of hip arthroplasty after 20 years (1), results in general orthopaedic units are unreported. Thirty-four patients with 45 primary cemented total hip arthroplasties implanted by “first generation” cementing techniques were reviewed after a mean of 20 years, documenting revision, occupation, and function. Twenty of the 35 (57%) hips were revised after a mean of 12 (2 to 21) years and reviewed after a mean of 7.6 years. Three hips had been subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Regardless of the reservations detailed in this study, the results of hip arthroplasty in younger patients are better than those previously reported with cemented total hip replacement, 51 in which there was a 14% revision rate after five years and 50% survival after 15 years. 52 Longer followup may establish whether the change of practice recorded here represents a true advance.…”
Section: Fig 8bmentioning
confidence: 82%
“…Regardless of the reservations detailed in this study, the results of hip arthroplasty in younger patients are better than those previously reported with cemented total hip replacement, 51 in which there was a 14% revision rate after five years and 50% survival after 15 years. 52 Longer followup may establish whether the change of practice recorded here represents a true advance.…”
Section: Fig 8bmentioning
confidence: 82%
“…This review demonstrated that only three factors related to treatment of joint disease have been investigated with regard to the patient’s return to work: type of operation, patient restrictions, and discharge based on guidelines. Based on the literature on TKA and THA, the following factors have been suggested to be important in optimizing return to work after TKA or THA: comorbidity [ 24 , 25 ], previous TKA or THA, or either revision [ 22 ], type of component used [ 26 28 ], kind of disease [ 29 , 30 ], and possible treatment after surgery [ 20 ]. It goes without saying that the factors already identified require extra research as well.…”
Section: Discussionmentioning
confidence: 99%